2011
DOI: 10.3233/rnn-2011-0612
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing recovery potential through simultaneous occupational therapy and non-invasive brain-stimulation using tDCS

Abstract: Purpose It is thought that following a stroke the contralesional motor region exerts an undue inhibitory influence on the lesional motor region which might limit recovery. Pilot studies have shown that suppressing the contralesional motor region with cathodal transcranial Direct Current Stimulation (tDCS) can induce a short lasting functional benefit; greater and longer lasting effects might be achieved with combining tDCS with simultaneous occupational therapy (OT) and applying this intervention for multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 51 publications
5
89
1
1
Order By: Relevance
“…Our results are consistent with several previous experimental (Allred et al, 2010; Rha et al, 2011; Zhao et al, 2009) and clinical (Boggio et al, 2007; Bradnam et al, 2011; Kang et al, 2011; Nair et al, 2011) studies, in which attenuating the effect of the contralesional hemisphere improved functional motor recovery after brain infarction. However, other experimental (Jin et al, 2011; Napieralski et al, 1998; Shanina et al, 2006) and clinical (Takeuchi et al, 2012) stroke studies have yielded opposite conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with several previous experimental (Allred et al, 2010; Rha et al, 2011; Zhao et al, 2009) and clinical (Boggio et al, 2007; Bradnam et al, 2011; Kang et al, 2011; Nair et al, 2011) studies, in which attenuating the effect of the contralesional hemisphere improved functional motor recovery after brain infarction. However, other experimental (Jin et al, 2011; Napieralski et al, 1998; Shanina et al, 2006) and clinical (Takeuchi et al, 2012) stroke studies have yielded opposite conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…We used random-effects model to account for this duplication (between-study variance τ 2 = 0.46; heterogeneity index I 2 = 71%). We grouped individual studies based on tDCS montage as anodal [24,25,28], cathodal [2325,27] or bihemispheric [22,26,29] (Fig. 2A) as well as based on the mean post-stroke duration as acute stroke [2325,28] or chronic stroke [22,26,27,29] (mean time post-stroke ≤1 month or ≥2.5 years, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of stimulation was not apparent across individuals with severe impairments who suffered from greater damage to CST from M1. Since the completion of the trial, several groups have continued to report no benefit of the classical approach (Hesse et al, 2011; Seniow et al, 2012; Talelli et al, 2012) even as others have evidenced a promising 5–6-point advantage in UEFM (Bolognini et al, 2011; Lindenberg, Renga, Zhu, Nair, & Schlaug, 2010; Nair, Renga, Lindenberg, Zhu, & Schlaug, 2011). Although, preliminary, we show that 5 of the 6 patients receiving facilitation to the ipsilesional premotor areas achieved clinically important gains ranging between 5 to 14-point increase in UEFM.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have emphasized a competitive role of the contralesional hemisphere (Marshall et al, 2000; Murase et al, 2004; N. S. Ward, Brown, Thompson, & Frackowiak, 2003a), seeking to decrease its excitability, hence its ability to overly-inhibit the ipsilesional hemisphere (Nair et al, 2011). However, controversy surfaced when studies with fMRI showed a greater shift in cortical activation to the contralesional hemisphere with greater gains after rehabilitative therapy (Cramer et al, 1997; Johansen-Berg, Dawes, et al, 2002).…”
Section: Discussionmentioning
confidence: 99%